PRACTICAL COURSE-CONFERENCE USING YOUTUBE AS INTERACTIVE TEACHING FORM OF PROFESSIONALS IN HIGHER EDUCATIONAL INSTITUTIONS - Khomik, Oksana; Kovalchuk, Oksana (Educological discourse, 2018)
The system of views on the problem of using interactive teaching methods in higher educational institutions has been considered in the article. The content of the concept “interactive teaching methods” has been revealed. The significance of practical course as the form of organization of educational interaction between the teacher and the students has been characterized. The role of the teacher and the students has been determined during practical courses-conferences. The procedure of conducting of interactive practical course-conference using YouTube has been described. The given examples of video materials, collected from YouTube for conducting practical course-conference on the theme “Language Etiquette” from the discipline “Management” have been given. The results of questioning of higher educational institutions’ teachers due to the conducting of their interactive practical course-conferences using YouTube have been introduced